Factors Affecting the Quality Service: A Case Study of SOCAR - Putri Natasha; Daisy Mui Hung Kee; Nadia Zulaikha; Siti Hajar Aisyah; Sharuweeswaran A/L Nagaraju; Akansha Rai; Rudresh Pandey (Advances in Global Economics and Business Journal, 2020)
The purpose of this study is to identify the factors affecting quality service by SOCAR. The researchers design a set of survey questions to collect data from randomly selected respondents around USM on the quality services provided by SOCAR. A total of 100 questionnaires were distributed but only 54 responses were collected. Based on the research conducted, most of the respondents in USM are not familiar with the usage of SOCAR, such as the proper procedure to rent a car via the SOCAR app. One of the factors that allow this problem to happen is competition with other companies such as Grab. The study results are expected to show a positive relationship between efficiency of quality services and passengers’ satisfaction.